"There and back again" : an examination of consumers' experiences of fantasy stories told through servicescape atmospherics : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University, Albany, New Zealand - Sadeghzadeh Fesaghandis, Kousar (Massey University, 2021)
The importance of fantasy as playful and imaginative consumption has been long noted by consumer researchers, often seen as the creation of extraordinary worlds that engage the consumers and provide them a pleasurable diversion and escape from the ordinary. While companies are increasingly coming to realise the value of fantasy and storytelling in engaging consumers and changing their emotions, behaviour, and brand perceptions, however, extant research in marketing are limited to brands and servicescapes that are marketed with an authentic story about the brand’s history or cultural stories. In addition, extant research focus on consumers’ engagement with stories presented in forms of texts, movies, and advertisements, with limited research conducted on the effects of storytelling through servicescape atmospherics. This thesis examined whether consumers experience narrative engagement in servicescapes that are designed based on fantasy stories, and how engagement with stories in servicescapes influences consumers’ emotions, behaviour, and brand personality perceptions. As consumers’ responses to a story differ depending on the story character they empathise with, this thesis, further, examined how empathy with positive (versus negative) story characters affects consumers’ subsequent responses in fantasy designed servicescapes. A sequential mixed-methods research design was employed in this thesis to address the research questions. Accordingly, the thesis begins by an exploratory qualitative enquiry conducting semi-structured in-depth interviews with retail design experts in Study 1 to understand circumstances in which implementing a fantasy story for design will be worth the effort, how the servicescape atmospherics are manipulated to present a given story, and the affective, behavioural, and brand responses designers aim to evoke in consumers in fantasy servicescapes. The researcher conducted semi-structured in-depth interviews with consumers in Study 2 to understand their experiences of engagement with stories, and subsequent responses in a fantasy designed servicescape. Based on the findings from the first two qualitative studies, the extracted propositions, together with existing scales and constructs in the literature, were replicated as part of the survey in Study 3 to examine the relationships between the servicescape atmospherics and consumers’ experiences of narrative engagement, their emotions and behaviour, and brand personality perceptions in a fantasy servicescape. Study 3, also, examined how consumers’ empathy with positive (versus negative) story characters influences their subsequent responses. This thesis contributes to environmental psychology, storytelling, narrative engagement, empathy, as well as the branding literatures and the findings have strong implications for retailers, design practitioners, and brand managers in terms of why, when, and how to use fantasy stories for designing servicescapes. Theoretically, the current thesis is the first to examine consumers’ engagement with and affective, behavioural and brand experiences in servicescapes that are designed based on a fantasy story. Based on the perceptions of both, the design experts as well as consumers, the researcher integrated narrative engagement (Busselle & Bilandzic, 2009) and empathy with characters (Van Laer, 2011) with Mehrabian and Russell’s (1974) SOR framework and brand personality (Aaker, 1997) and made a significant contribution by developing a framework that can help future studies examine consumers’ experiences of fantasy stories in servicescapes. The results of the three conducted studies were consistent in suggesting that consumers experience narrative engagement in servicescapes that are designed upon a fantasy story, and that the narrative presence dimension of narrative engagement can, by itself, explain the process underlying the effect of stories told through the atmospherics on consumers’ emotions, behaviour, and brand personality perceptions. Regardless of the character type (positive versus negative) the servicescape highlighted, consumers engaged to the same extent with the story, and experienced more positive and less negative emotions as a result of engagement with the story. Engagement with stories, further, positively affected consumers’ behavioural intentions. Higher levels of empathy with a story character, however, negatively affected consumers’ behavioural intentions, regardless of the character the servicescape highlighted. Accordingly, the design experts recommend using fantasy elements at a moderate level for design to attract not only fans but also non-fan consumers to the servicescape, enhance consumers’ engagement with the retailer’s offer, and increase return intention. Moreover, engagement with the story in the servicescape highlighting the negative character positively affected brand personality, with higher levels of empathy with the negative character strengthen brand personality. Featuring negative characters in a servicescape thus results in stronger brand experience. Finally, while product and service providing businesses both, benefit from using stories for their servicescape design, story-based designs were found to be most effective when the story is congruent with and therefore, supports the products or services offered.
Keywords: Consumer satisfaction; Customer relations; Fantasy; Retail trade; 350602 Consumer-oriented product or service development